Ethnopedagogy: Study of The Alms of The Earth Tradition as Strengthening the Character Education of Social Knowledge in Junior High Schools - Hidayati, Armawati; Khusnul Khotimah; Miftakhul Huda; Bayu Kurniawan (Universitas Negeri Surabaya, 2023)
Made is a sub-district located in the city of Surabaya, due to its area, nuance, and natural conditions that are similar to the countryside, causing this sub-district to be called by the local community as Made Village. Even though they are in the middle of an urban community that supports companionship, the residents of Made Village have a community structure with a high level of tolerance and mutual cooperation, this can be seen during the traditional ceremony of alms of earth which is carried out routinely every year by the people of Made Village. With the values of tolerance, mutual cooperation, and cultural values that are reflected in the structure of the Made Village community, this can become provision for strengthening character and cultural education in classroom learning. The method in this study uses a qualitative approach with data collection techniques through interviews and field observations. The tradition of almsgiving in Made Village is one of the things highlighted in this research. This tradition requires the cooperation and cohesiveness of all local residents, considering that its implementation takes place over three days and three nights with various series of events. Through research on the tradition of the earth alms tradition in Made Village, it is known that it has pedagogical values, namely, respecting nature, living in harmony side by side, tolerance, mutual cooperation, and maintaining and preserving culture, which can be implemented as strengthening character education in junior high schools.